Assessment of Parental Quality of Life in Febrile Seizures Using Pediatric Quality of Live Inventory Parental Report - Octavius, Gilbert Sterling; Virliani, Cindy; Juliansen, Andry (Journal of Pediatric Epilepsy, 2021)
Febrile seizure (FS) is the most common convulsive disorder in children with FS prevalence in Indonesia reaching 2 to 4% in 2008. Although this entity has a good prognosis, it often brings panic, fear, and anxiety to the parents. This seemingly benign condition might lead to changes in family structures resulting in adverse effects on the family's daily lives and affect their overall quality of life (QoL). This study evaluates the QoL of parents whose children have FS. A cross-sectional study done in 47 parents whose children had a FS between ages 1 and 4 years from January 2020 to May 2020 and who were evaluated at the Siloam General Hospital, Lippo Village. Parents were asked to fill in Pediatric Quality of Life Questionnaire parent proxy. Data normality was analyzed using the Shapiro–Wilk's test and the significant impact of parents' QoL using the chi-square and independent t-tests. From a total of 47 parents, 30 (63.8%) parents had children with simple FS and 17 (36.2%) parents had children with complex FS. Parents whose children were in the age group of 1 year to 1 year 11 months had the best mean score of 79.64 (12.17) compared with other age groups. In the subset of 3 to 4 years old, the daily activities domain was significantly affected (p-value = 0.3). Parents with a lower educational level had a higher mean score of 76.53 (14.42) than parents who had a higher educational level, with a total mean of 79.88 (11.85), particularly with the highest mean score of 100 in the communication domain. The occurrence of FSs in children affected their parents' QoL in almost all domains in the Pediatric Quality of Life Inventory questionnaire.
Keywords: febrile seizure; quality of life; parents